Translation and validation of a Bahasa Malaysia (Malay) version of the Multidimensional Assessment of Interoceptive Awareness (MAIA) - Todd, Jennifer; Barron, David; Aspell, Jane E.; Toh, Evelyn Kheng Lin; Zahari, Hanoor Syahirah; Khatib, Nor Azzatunnisak Mohd.; Swami, Viren (PLOS ONE, 2020)
Objectives The 32-item Multidimensional Assessment of Interoceptive Awareness (MAIA) is a widely-used measure of multidimensional interoception. In the present study, we examined the psychometric properties of a Bahasa Malaysia (Malay) translation of the MAIA. Methods An online sample of 815 Malaysian Malays (women n = 403) completed a novel translation of the MAIA. Validated measures of trait mindfulness and self-esteem were also completed to facilitate a preliminary assessment of convergent validity. Results Exploratory factor analysis indicated that the MAIA items reduced to a 19-item, 3-factor model. The 3-factor model was further tested using confirmatory factor analysis (CFA) alongside the parent 8-factor model. Both models had good fit on some indices, but less-than-ideal fit on other indices. The 3-factor model evidenced comparatively better fit, with fit indices being adequate following modification. Multi-group CFA indicated both the 3-factor model and the 8-factor model had full strict invariance across sex. However, evidence for construct and convergent validity was mixed. Conclusions Overall the 3-dimensional Malay MAIA was demonstrated to be both internally consistent and invariant across sex, but further evidence of construct and convergent validity is required. Issues that affect the dimensionality of MAIA scores in the present and extant work are discussed in conclusion.